2011
DOI: 10.1016/j.jmii.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Mortality predictors of Pneumocystis jirovecii pneumonia in human immunodeficiency virus-infected patients at presentation: Experience in a tertiary care hospital of northern Taiwan

Abstract: HIV-infected patients with PJP can be clinically stratified by three prognostic variables identified by multivariate analysis. Early recognition of patients in higher risk can assist clinicians to prevent rapid deterioration and seek for better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
1
16
0
2
Order By: Relevance
“…When CXR is at the mid stage, chest CT may be at the early- or mid-stage. In the mid stage, the patients usually present with obvious dyspnea and hypoxemia,[13] and then clinicians just recognize the diagnosis of PCP, although PCP in patients without AIDS was diagnosed after a shorter time interval from symptom onset. [8] Our study showed that the CFR of PCP is significantly higher when specific anti-PCP treatments begin in the mid stage rather than early stage.…”
Section: Discussionmentioning
confidence: 99%
“…When CXR is at the mid stage, chest CT may be at the early- or mid-stage. In the mid stage, the patients usually present with obvious dyspnea and hypoxemia,[13] and then clinicians just recognize the diagnosis of PCP, although PCP in patients without AIDS was diagnosed after a shorter time interval from symptom onset. [8] Our study showed that the CFR of PCP is significantly higher when specific anti-PCP treatments begin in the mid stage rather than early stage.…”
Section: Discussionmentioning
confidence: 99%
“…An association of this comorbidity factor with an increased risk for death has already been reported ( 24 , 25 ). Several other clinical parameters were reported to be predictors for death caused by PCP in HIV-infected patients ( 26 ), and a scoring tool was recently proposed ( 27 ). Host polymorphisms within receptors involved in the immune response have also been reported to be related to P. jirovecii infection ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of death remains to be PJP, a preventable disease if HAART with/without PJP prophylaxis is initiated early enough [1,3]. Despite good adherence to PJP treatment guidelines, mortality rates remain high, between 35-40% [15,16].…”
Section: Discussionmentioning
confidence: 99%